Supporting Student's Ability in Understanding Least Common Multiple (LCM) Concept Using Storytelling - Triyani, Septi; Darmawijoyo, Darmawijoyo; Putri, Ratu Ilma Indra (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
Several researches showed that students had difficulty in understanding the concept of Least Common Multiple (LCM) in Elementary School. This underlies the researcher to design a learning of LCM using storytelling, Legend Putri Dayang Merindu (LPDM), which contains situational problem related to LCM. The purposes of this study are to know the role of LPDM in supporting students' ability to understand LCM concept and to generate a student learning trajectory in learning of LCM using LPDM. This research uses methodology of design research consists of three steps (i.e. preliminary design, teaching experiment andÂ retrospective analysis), and the learning approach of realistic mathematics education, labeled by PMRI in Indonesia. From the research result conducted in MIN 1 Palembang can be concluded that the learning of LCM using LPDM has role in supporting students' ability to understand LCM concept. Therefore, student learning trajectory to understanding LCM concept is started from solving of situational problems based on LPDM until formal solution of LCM. In this case, there are three stages that students through (i.e. understanding concept of multiple, common multiple and LCM) using various strategies in the level situational, model of, model for and formal.